DNAJC3 deficiency induces β-cell mitochondrial apoptosis and causes syndromic young-onset diabetes. Issue 3 (March 2021) - Lytrivi, Maria; Senée, Valérie; Salpea, Paraskevi; Fantuzzi, Federica; Philippi, Anne; Abdulkarim, Baroj; Sawatani, Toshiaki; Marín-Cañas, Sandra; Pachera, Nathalie; Degavre, Anne; Singh, Pratibha; Derbois, Céline; et al.
Abstract : Objective: DNAJC3, also known as P58 IPK, is an Hsp40 family member that interacts with and inhibits PKR-like ER-localized eIF2α kinase (PERK). Dnajc3 deficiency in mice causes pancreatic β-cell loss and diabetes. Loss-of-function mutations in DNAJC3 cause early-onset diabetes and multisystemic neurodegeneration. The aim of our study was to investigate the genetic cause of early-onset syndromic diabetes in two unrelated patients, and elucidate the mechanisms of β-cell failure in this syndrome. Methods: Whole exome sequencing was performed and identified variants were confirmed by Sanger sequencing. DNAJC3 was silenced by RNAi in INS-1E cells, primary rat β-cells, human islets, and induced pluripotent stem cell-derived β-cells. β-cell function and apoptosis were assessed, and potential mediators of apoptosis examined. Results: The two patients presented with juvenile-onset diabetes, short stature, hypothyroidism, neurodegeneration, facial dysmorphism, hypoacusis, microcephaly and skeletal bone deformities. They were heterozygous compound and homozygous for novel loss-of-function mutations in DNAJC3 . DNAJC3 silencing did not impair insulin content or secretion. Instead, the knockdown induced rat and human β-cell apoptosis and further sensitized cells to endoplasmic reticulum stress, triggering mitochondrial apoptosis via the pro-apoptototic Bcl-2 proteins BIM and PUMA. Conclusions: This report confirms previously described features and expands the clinical spectrum of syndromic DNAJC3 diabetes, one of the five monogenic forms of diabetes pertaining to the PERK pathway of the endoplasmic reticulum stress response. DNAJC3 deficiency may lead to β-cell loss through BIM- and PUMA-dependent activation of the mitochondrial pathway of apoptosis.